Parenting Styles and Temper Tantrum among Preschool Children: A Cross-Sectional Study - Lidya; Nusi, Tezar; Laya, Agust Arthur (Bantayang Omni Cendekia, 2026)
Background: Temper tantrum is a common emotional response in preschool children and is often influenced by parenting styles applied by parents in daily life. Inappropriate or inconsistent parenting may increase the frequency and intensity of temper tantrum behavior, which can negatively affect children’s emotional and social development. Objective: This study aimed to determine the relationship between parenting styles and temper tantrum among preschool children. Methods: This study employed a quantitative correlational design with a cross-sectional approach. The population consisted of parents and preschool children aged 4–6 years at a kindergarten in Manado, North Sulawesi province, Indonesia, with a total sample of 32 respondents selected using total sampling. Data were collected using structured questionnaires measuring parenting styles and temper tantrum levels. Data were analyzed using univariate and bivariate analysis with the Spearman Rank correlation test. Results: The majority of parents applied a moderate parenting style category (56.3%) and most preschool children experienced temper tantrum at a moderate level (71.9%). Spearman Rank test showed a statistically significant moderate positive correlation between parenting styles and temper tantrum (rs = 0.502, p < 0.05). Conclusion: Parenting style is significantly associated with temper tantrums among preschool children. Improving parenting practices may help reduce temper tantrum behaviors in preschool children.